Recurrent posterior shoulder instability—Long‐term results after arthroscopic posterior bone block with capsular reconstruction - Roman F. Karkosch; Juergen Slapar; Tomas Smith; Mathias Wellmann; Marc‐Frederic Pastor; Hauke Horstmann (Journal of Experimental Orthopaedics)
Abstract Purpose This study reports the long‐term post‐operative clinical outcomes after arthroscopic posterior bone block augmentation with posterior capsular repair. Methods Eighteen shoulders (13 patients) with unidirectional posterior shoulder instability were treated with an arthroscopic posterior bone block augmentation and posterior capsular repair in 2011 and 2013 in a single specialized orthopaedic clinic. These patients were invited to participate in a clinical and radiological follow‐up examination to receive long‐term results regarding clinical outcomes, instability, and development of osteoarthritis (OA). Results From the initial study group, 13 patients (18 shoulders) could be obtained for a follow‐up examination. The mean follow‐up period was 111 months. At the final follow‐up, two patients (two shoulders) reported recurrent subluxations with a positive apprehension sign. No redislocation was reported. Screw fixation was still in place in seven patients (38.9%). Overall, good clinical outcomes were achieved among Constant–Murley score (77.6 ± 16; p = 0.55), Rowe score (67.5 ± 22.1; p = 0.34), Walch–Duplay score (58.3 ± 28.2) and Western Ontario Shoulder Index (40.4 ± 23.3%; p = 0.96), showing insignificant changes compared with the 2‐year results. Three shoulders developed severe OA (Samilson and Prieto III). No patient required arthroplasty. Conclusion Arthroscopic posterior bone block augmentation with posterior capsular repair represents a salvage procedure that can achieve long‐term shoulder stability with overall moderate clinical results. Patients have to be informed about the probable need for implant removal and the high risk of OA development, especially in the presence of pre‐existing cartilage damage, beforehand. Level of Evidence Level IV.